The Phytochemical Investigation and Biological Activities of Berberis Orthobotrys - Akber Dad; Iftikhar Ali; Nadja Engel; Muhammad Atif; Hidayat Hussain; Viqar Uddin Ahmad; Ivan R. Green (International Journal of Phytomedicine, 2017)
The leaf extract of Berberis orthobotrys Bien. ex Aitch. (B.o.) afforded three compounds viz., β-sitosterol (1), sesamin (2) and 10-eicosanol (3) which were identified by spectroscopic methods including 1D and 2D NMR, GC-MS, IR and comparison of their spectral data with the published data. To the best of our knowledge these three compounds are reported here for the first time to be isolated from Berberis orthobotrys Bien. ex Aitch. (B.o.). Moreover the root extract exhibited good antilieshmanial activity and root and fruit extracts demonstrated minor antifungal activity against Fusarium solani.